Collecting information on job tasks—an instrument to measure tasks required at the workplace in a multi-topic survey - Britta Matthes; Bernhard Christoph; Florian Janik; Michael Ruland (Journal for Labour Market Research, 2014)
The analysis of job tasks has become a field of growing scientific activity in recent years. Information on such tasks has been used to analyze various research questions, especially regarding changes in the overall structure of the economy and their implications for persons and firms. Arguably the most prominent of these research questions is the analysis of the consequences of technological change for job tasks, skill demand, and wage inequality. Despite the growing importance of this field of research, the range of actual task measures to be used in empirical analyses is rather limited. Therefore, we considered it worthwhile to develop a survey instrument to measure job tasks by asking the job holders directly. The resulting questionnaire module was administered in the fourth panel wave of the German National Educational Panel Study's (NEPS) adult stage. In this paper, we provide an overview of our conceptual background as well as the steps taken during the development of the survey instrument. Furthermore, we present an initial exploratory analysis of the data collected to validate the instrument.
Keywords: C89; J23; O33; 330; Tätigkeitsanalyse; Tätigkeitsmerkmale; Arbeitsanforderungen; Datengewinnung; Fragebogen; Validität; Stellenbeschreibung; Berufsanforderungen; Qualifikationsmerkmale; Qualifikationsanforderungen; Routine; Interaktion; manuelle Arbeit; Nationales Bildungspanel